INFLUENCE OF NURSERY EDUCATION ON COGNITIVE COMPETENCE AMONG PUPILS IN PUBLIC PRIMARY SCHOOLS IN SOKOTO STATE. DOES IT PERSIST OR FADE? - Bagudo, Asiyatu Abubakar (Sokoto Educational Review, 2013)
This study used survey research to examine the relationship in performances of pupils with nursery education in cognitive competence across the first three years of primary school in Sokoto State. The aim was to find out if the academic gains of nursery education are sustained or diminished through the first three years in primary school. The stratified random sample was used to choose 300 boys and 300 girls. A self-designed, validated and reliable instrument on cognitive competence was used. One null hypothesis was generated and tested using regression statistics. The hypothesis was rejected because the study found significant coherence in the cognitive competence of pupils across the first three years in primary school. The study recommends stakeholders to provide complementary quality education and linkage between nursery and primary education and to ensure that psycho-social and character assessments are conducted and included in result reports and certificates as evidence of learning outcomes attained by learners.